2007
DOI: 10.1002/jcb.21608
|View full text |Cite
|
Sign up to set email alerts
|

N‐Glycosylation affects the adhesive function of E‐Cadherin through modifying the composition of adherens junctions (AJs) in human breast carcinoma cell line MDA‐MB‐435

Abstract: E-cadherin mediates calcium-dependent cell-cell adhesion between epithelial cells. The ectodomain of human E-cadherin contains four potential N-glycosylation sites at Asn residues 554, 566, 618, and 633. In this study, the role of N-glycosylation in E-cadherin-mediated cell-cell adhesion was investigated by site-directed mutagenesis. In MDA-MB-435 cells, all four potential N-glycosylation sites of human E-cadherin were N-glycosylated. Removal of N-glycan at Asn-633 dramatically affected E-cadherin stability. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…However, little is known about the post-transcriptional modifications of E-cadherin and its role in E-cadherin-mediated tumor progression in gastric cancer cells. A substantial body of evidence has appeared to support the view that the E-cadherin function may mainly be affected by mechanisms through N-glycosylation at the post-translational level in some carcinomas (37)(38)(39). However, our data demonstrated that downregulation of GnT-V affected the transcripts of E-cadherin and vimentin, and further influenced the protein expression of E-cadherin and vimentin.…”
Section: Expression Of Invasion-related Factors In the Bgc823/gnt-v Cmentioning
confidence: 48%
“…However, little is known about the post-transcriptional modifications of E-cadherin and its role in E-cadherin-mediated tumor progression in gastric cancer cells. A substantial body of evidence has appeared to support the view that the E-cadherin function may mainly be affected by mechanisms through N-glycosylation at the post-translational level in some carcinomas (37)(38)(39). However, our data demonstrated that downregulation of GnT-V affected the transcripts of E-cadherin and vimentin, and further influenced the protein expression of E-cadherin and vimentin.…”
Section: Expression Of Invasion-related Factors In the Bgc823/gnt-v Cmentioning
confidence: 48%
“…Although there might be different interpretations of the structural basis of these experimental observations, the results presented here are consistent with a process in which adhesion triggers subsequent changes in cadherin organization at cell-cell junctions that further enhances binding and is modulated by N-glycans. This study focused on N-cadherin glycosylation, but E-cadherin hyper-glycosylation has been implicated in cadherin dysfunction in cancer (de Freitas Junior et al, 2011;Geng et al, 2004;Pinho et al, 2009a;Pinho et al, 2011;Zhao et al, 2008a). Although phenotypic changes of E-cadherin hypo-glycosylation (Jamal et al, 2009;Nita-Lazar et al, 2010) are qualitatively similar to those reported for N-cadherin (Guo et al, 2009), the glycosylation sites with the greatest impact on E-cadherin-based cell functions appear to be on membrane proximal domains EC4-EC5 (Liwosz et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…A large number of studies link aberrant glycosylation to altered cadherin-dependent cell functions, in the context of different cancers. Phenotypic changes include altered cell motility in scratch-wound healing assays, cytoskeleton reorganization, metastasis, ERK signaling and barrier function (Bajpai et al, 2008;Guo et al, 2009;Jamal et al, 2009;Liwosz et al, 2006;Pinho et al, 2009a;Pinho et al, 2011;Vagin et al, 2008;Zhao et al, 2008a). In the case of N-cadherin, the N-glycosylation sites at N273, N325 and N402 are highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Junctional stability is associated with a switch in cadherin conformation (44,45), and it is possible that recruitment to the galectin lattice may impede clustering and alter N-cadherin conformation and recruitment of intracellular partners. Indeed, it was shown that E-cadherin hyperglycosylation results in immature and less stable cell adhesions due to increased spacing between dimers and differential recruitment of intracellular partners at cell-cell contacts (46,47).…”
Section: Discussionmentioning
confidence: 99%